Possibilities for the introduction of legumes in dairy sheep feeding in Northern Evros (Greece) - Manousidis T.; Ragkos A.; Abas Z. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The debate about legume crops is becoming more relevant, mainly because the changes in the Common Agricultural Policy have increased their competitiveness against other crops. Indeed, they constitute a low-cost alternative source of protein for animal nutrition. The purpose of this study is to report the findings of an experiment regarding the introduction of legumes in sheep nutrition in Northern Evros, Greece. Two alternative feed mixtures were provided to two groups of 35 Lacaune sheep; the first mixture included soybean meal and the second faba bean (Vicia faba L.) meal as main sources of protein. The two alternative mixtures were equal in terms of energy and protein content. Milk production was recorded for all animals every 7 days and the milk was analysed for its chemical composition. The results indicate only significant differences in the protein content of milk. Economic benefits of the introduction of legumes in sheep nutrition are accounted for through partial budgeting. The generalized introduction of legumes in sheep nutrition is linked to the achievement of higher crop yields, as they are currently rather low. In addition, collaboration between farmers and livestock producers, or even on-farm production by the latter, will induce a widespread cultivation of legumes in the area.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)